HCA587 Protein Vaccine Induces Specific Antitumor Immunity Mediated by CD4+ T-cells Expressing Granzyme B in a Mouse Model of Melanoma - Yang, Weiming; Zhang, Weiheng; Wang, Xiaozhong; Tan, Liming; Li, Hua; Wu, Jiemin; Wu, Qiong; Sun, Wanlei; Chen, Juanjuan; Yin, Yanhui (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: The antigen HCA587 (also known as MAGE-C2), which is considered a cancer-testis antigen, exhibits upregulated expression in a wide range of malignant tumors with unique immunological properties, and may thus serve as a promising target for tumor immunotherapy. Objective: The study aimed to explore the antitumor effect of the HCA587 protein vaccine and the response of humoral and cell-mediated immunity. Methods: The HCA587 protein vaccine was formulated with adjuvants CpG and ISCOM. B16 melanoma cells were subcutaneously inoculated to C57BL/6 mice, followed by treatment with HCA587 protein vaccine subcutaneously. Mouse survival was monitored daily, and tumor volume was measured every 2 to 3 days. The tumor sizes, survival time and immune cells in tumor tissues were detected. And the vital immune cell subset and effector molecules were explored. Results: After treatment with HCA587 protein vaccine, the vaccination elicited significant immune responses, which delayed tumor growth and improved animal survival. The vaccination increased the proportion of CD4+ T cells expressing IFN-γ and granzyme B in tumor tissues. The depletion of CD4+T cells resulted in an almost complete abrogation of the antitumor effect of the vaccination, suggesting that the antitumor efficacy was mediated by CD4+ T cells. In addition, knockout of IFN-γ resulted in a decrease in granzyme B levels, which were secreted by CD4+ T cells, and the antitumor effect was also significantly attenuated. Conclusion: The HCA587 protein vaccine may increase the levels of granzyme B expressed by CD4+ T cells, and this increase is dependent on IFN-γ, and the vaccine resulted in a specific tumor immune response and subsequent eradication of the tumor.
Keywords: HCA587 protein vaccine